Health Belief Model of Pregnant Women in Samarinda’s Free Nutritious Meal Program: The Role of Predisposing, Reinforcing, and Enabling Factors in Self-Efficacy - Tri Sunarsih; Rosdiana Rosdiana; Nendhi Wahyunia Utami; Endah Puji Astuti; Elvika Fit Ari Shanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Stunting remains a national health priority in Indonesia due to its long-term impact on human capital. One flagship government intervention under the National Strategy for Stunting Reduction 2018–2024 is the provision of free nutritious meals for pregnant women to improve maternal nutritional status and prevent stunting. However, adherence to this program varies widely, and previous studies have rarely examined psychosocial determinants based on behavioural health theories. Objective: This study aimed to analyse factors within the Health Belief Model (HBM), including perceived susceptibility, severity, benefits, barriers, cues to action, and self-efficacy, alongside predisposing, reinforcing, and enabling factors that influence the self-efficacy of pregnant women participating in the free nutritious meal program in Samarinda City. Methods: A quantitative cross-sectional design was applied to 203 pregnant women enrolled in the free nutritious meal program between March and August 2024. Participants were selected purposively to ensure representation of diverse educational backgrounds, parity, and gestational ages according to predefined inclusion criteria. Data were collected using a structured questionnaire based on HBM dimensions, perceived susceptibility, severity, benefits, barriers, cues to action, and self-efficacy, that had been validated and tested for reliability. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was employed due to its suitability for analyzing complex latent constructs and small-to-moderate sample sizes, enabling simultaneous estimation of measurement and structural models. Results: Predisposing factors showed a strong effect on the HBM construct (? = 0.556). Reinforcing factors exerted a greater influence on self-efficacy (? = 0.228) compared with enabling factors (? = 0.142). The HBM construct itself contributed positively to the enhancement of self-efficacy (? = 0.244). The model demonstrated an SRMR of 0.074 (< 0.08), indicating acceptable model fit. Conclusion: Predisposing factors (knowledge, attitudes, and motivation) form the foundation of maternal health perceptions, while social support (reinforcing factors) plays a more dominant role than enabling factors in improving pregnant women’s self-efficacy. This first comprehensive application of the HBM to a free nutritious meal program in Samarinda provides new empirical evidence to guide the design of theory-based maternal nutrition interventions and supports Indonesia’s national stunting reduction efforts. Theoretically, the findings extend the HBM by demonstrating how contextual predisposing and reinforcing factors interact to strengthen self-efficacy within community-based nutrition programs. Practically, policymakers should integrate behavioral counseling and family involvement components into the free meal program to enhance motivation and sustained adherence among pregnant women. Future research should use longitudinal designs to assess long-term program effects and explore contextual factors influencing self-efficacy.